Changes in implicit and explicit exercise-related attitudes after reading targeted exercise-related information. (January 2016) - Berry, Tanya R.
Abstract: The purpose of this research was to examine if reading exercise information targeted at pretest explicit attitudes were related to changes in corresponding implicit or explicit attitudes. The associative-propositional evaluation (APE) model guided the research. Participants ( N = 154) completed pretest measures of implicit and explicit attitudes; one week later they read information that targeted pretest explicit affective or instrumental attitudes and again completed the attitude measures. Results showed changes in implicit attitudes in both instrumental message conditions that supported the hypotheses that counter-attitudinal information would result in implicit attitude change in the opposite direction to the reading whereas information that targeted congruent attitudes would show changes in keeping with the information. This study demonstrates the importance of considering how implicit cognitions may change as a result of reading exercise-related information, and the relationship between implicit and explicit attitudes. Highlights: This study provides important information about how implicit and explicit attitudes may change. Exercise-related materials can lead to short-term explicit attitude change. Counter-attitudinal information may result in ironic activation of associations. Information that targets positive attitudes activates congruent associations.